Community Ethnography for Understanding Social Dynamics in Migration - Djufri (Indonesian Journal Publisher, 2025)
This study aims to explore how migrant communities construct, sustain, and negotiate social structures in urban environments. Using a community ethnography approach, the research is grounded in Anthony Giddens' structuration theory and Pierre Bourdieu’s concept of socio-cultural capital. The research was conducted in Tamalate District, Makassar, involving participatory observation and in-depth interviews with 15 key informants. Findings reveal that social structures within migrant communities emerge from routinized daily practices such as communal gatherings, religious study groups, and collective neighborhood maintenance. Socio-cultural capital—manifested in networks, trust, and shared values—significantly influences individuals’ positions and roles in the community. Moreover, the younger generation is actively involved in shaping new socio-cultural spaces through digital adaptation and small-scale entrepreneurship. Migrant communities also employ symbolic strategies to navigate external challenges without engaging in open conflict, which reflects a form of silent resistance and social negotiation. This study highlights the remarkable adaptability and resilience of migrant communities in urban settings. Rather than being passive subjects of displacement, these communities actively reproduce and transform their social world, contributing to a dynamic and empowered urban life. The findings offer valuable insights into the interplay between migration, identity formation, and urban inclusivity, emphasizing the importance of culturally sensitive approaches in urban development policies